PENGARUH STRUKTUR MODAL, SISTEM INFORMASI AKUNTANSI, DIGITAL MARKETING TERHADAP KINERJA UMKM DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL PEMODERASI - Althafa, Erchika Destiara; Farida, Yusriati Nur; Suparlinah, Irianing (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2023)
This research aims to determine the effect of capital structure, accounting information systems, and digital marketing on the performance of MSMEs with organizational culture as a moderating variable. This method used in this research is quantitative research. The population of this study were all MSMEs in Banyumas Regency. The sample determination was determined by purposive sampling with a total sample of 100 MSME units. Data analysis that was used is moderation regression analysis. The results showed that: (1) capital structure has no effect on MSME performance; (2) accounting information systems has no effect on MSME performance; (3) digital marketing has no effect on MSME performance; (4) organizational culture has no effect on MSME performance; (5) capital structure has no effect on MSME performance through organizational culture; (6) accounting information systems affect MSME performance through organizational culture; and (7) digital marketing has no effect on MSME performance through organizational culture. The implication of this research is that MSME can pay more attention to the use of capital structure, accounting information systems, digital marketing and organizational culture in their efforts to improve MSME performance. For the government, it is expected to hold socialization and training on capital structure, accounting information systems, and digital marketing to support the performance of MSMEs.